Fenomena Pentakdisan Turāth di Dayah Tradisional Aceh: The Sacralization of Turāth at Traditional Dayah of Aceh - Muhammad Latif, Lazuardi; Ahmad Shah, Faisal (Jurnal Usuluddin, 2021)
The sacralization of turāth refers to a form of unconditional admiration toward and blind acceptance of the content of turāth books, with the assumption that the books are free of mistakes or inaccuracies. The traditional Dayah of Aceh, a highly valued educational Islamic institution in the eyes of the Acehnese people, plays a pivotal role in promoting various religious understandings as prescribed in turāth books. In order to see to what extent this assumption is true, this field study attempts to investigate the use of turāth at Dayah Mudi Mesra, Samalanga, Aceh. This Dayah has earned much respect and trust from today's Acehnese society due to its role in the teaching of Fikah. The study was carried out to identify the perceptions of the ulama at the traditional dayah toward the position of turāth books in their study of Islamic sciences, especially fikah. This qualitative study employs various data collection methods including literature review, interviews, documentation and observations. In addition, inductive, deductive, and comparative methods were used for data analysis. The study found that the ulama of the traditional dayah in Aceh, in their studies of Islamic sciences, especially fikah, had regarded turāth books as being on par with hadith.